Response Time Analysis of Messages in Controller Area Network: A Review. (10th January 2013) - Mary, Gerardine Immaculate; Alex, Z. C.; Jenkins, Lawrence
Abstract : This paper reviews the research work done on the response time analysis of messages in controller area network (CAN) from the time CAN specification was submitted for standardization (1990) and became a standard (1993) up to the present (2012). Such research includes the worst-case response time analysis which is deterministic and probabilistic response time analysis which is stochastic. A detailed view on both types of analyses is presented here. In addition to these analyses, there has been research on statistical analysis of controller area network message response times.